Decreased iKIR-HLA C Pair Confers Worse Clinical Outcomes for Patients With Myeloid Disease Receiving Antithymocyte Globulin-Based Haploidentical Hematopoietic Stem Cell Transplantation - Zhao, Yanmin; Gao, Fei; Wu, Yibo; Shi, Jimin; Luo, Yi; Tan, Yamin; Yu, Jian; Lai, Xiaoyu; Zhang, Mingming; Zhang, Wei; Huang, He (Frontiers in Immunology, 2021)
Hematopoietic stem cell transplantation (HSCT) is a curative therapy for patients with malignant hematologic diseases. Killer immunoglobin-like receptor (KIR) expressed by NK cells is closely associated with the transplant outcomes, and it has been widely explored and debated for a few decades. Recently published investigations have revealed that inhibitory KIRs (iKIRs) are educated by their cognate HLA ligands, and that decreased iKIR-HLA pairs post-transplantation may indicate a reduced NK cell function and impaired control of the primary disease. However, this theory still needs to be validated by additional clinical studies. Here we conducted a retrospective analysis of 246 patients who received haploidentical (haplo)-HSCT at our treatment center between January 2015 and June 2018. Our data suggests that decreased iKIR-HLA C pair post-HSCT correlated with a significantly higher risk of relapse (HR=2.95, p=0.019) and reduced overall survival (OS) (HR=3.74, p=0.001) and disease-free survival (DFS) (HR=4.05, p=0.0004) in patients with myeloid disease. In conclusion, decreased iKIR-HLA C pair should be avoided during anti-thymocyte globulin (ATG)-based haplo-HSCT, especially for patients with myeloid disease.